Acoustic technics - Ihde, Don, 1934- (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc, 2015)
Acoustic Technics, aware that digital and computer embedded technologies produce data that today can be transformed into acoustic images, notes the transformations these phenomena imply for a diverse set of practices, such as music, communication, medical diagnosis, and scientific knowledge.